دراسة تحليلية لاقتصاديات الموارد المائية - محمود حبيب; الصايغ كارول (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف هذا البحث إلى إلقاء الضوء على الخصائص الاقتصادية المميزة للموارد المائية، كما يهدف إلى تحديد الأسباب التي أدت لزيادة الاهتمام بدراسة الموارد المائية واقتصادياتها. وبالاعتماد على المنهج الوصفي التحليلي من خلال توصيف ما هو قائم وتحليله، حاولت الباحثة الوقوف على السياسات الواجب اتباعها لتخصيص أرصدة المياه بين الفترات الزّمنية، وتحديد فيما إذا كان مورد المياه مورد اقتصادي ويخضع لآليات السّوق (العرض، والطلب)، حيث أشارت نتائج البحث إلى كون مورد المياه مورد حيوي استراتيجي، ومن الخيرات الاقتصادية ذات الطبيعة الخاصة التي تجعل منه مورداً غير خاضع لآليات السوق، وتمثلت توصيات البحث بضرورة الاهتمام باقتصاديات الموارد المائية للوصول إلى الكفاءة في استغلال المورد لتحقيق استدامته من جهة، ولتحقيق التنمية الاقتصادية من جهةٍ أخرى. This research aims to shed a light on the distinctive economic characteristics of water resources and to identify the reasons that led to increasing interest in studying these resources and their economics. depending on descriptive analytical method through characterization of what is and analyze it, The researcher is addressing the policies necessary to be followed for a successful allocation of water balances within the time periods, and define whether the water resources are to be considered as an economical good and whether they are subjected to market mechanisms, i.e. demand and supply. the research results pointed out to the fact that the water resource is a strategic vital resource and an economic good has a special nature which make it not subject to market mechanisms. this study is providing a number of proposals that emphasize the need to focus on the economics of water resources to attain the efficiency of resource exploitation, which, on the one hand, leads to achieving sustainability of this valuable resource, and on the other hand fulfill maintain the economic development.